2020
DOI: 10.21203/rs.3.rs-73986/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Developmental Cell Atlas: milestones achieved and the roadmap ahead

Abstract: The Human Developmental Cell Atlas (HDCA), as part of the Human Cell Atlas, aims to generate a comprehensive reference map of cells during development. This detailed study of development will be critical for understanding normal organogenesis, the impact of mutations, environmental factors and infectious agents on congenital and childhood disorders, and the molecular cellular basis of ageing, cancer and regenerative medicine. In this perspective, we outline the challenges of mapping and modelling human develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Therefore, most skin studies have used murine models, resulting in a lack of mechanistic insight into the specification of cell types during human development. International consortium efforts to map developing cell lineages in organoids and human fetal tissue should shed light on these mechanisms 40,41 . Single-cell sequencing approaches, such as RNA sequencing and assay for transposase-accessible chromatin (ATAC) using sequencing, can be performed on skin organoids.…”
Section: Applications Of the Skin Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, most skin studies have used murine models, resulting in a lack of mechanistic insight into the specification of cell types during human development. International consortium efforts to map developing cell lineages in organoids and human fetal tissue should shed light on these mechanisms 40,41 . Single-cell sequencing approaches, such as RNA sequencing and assay for transposase-accessible chromatin (ATAC) using sequencing, can be performed on skin organoids.…”
Section: Applications Of the Skin Organoidsmentioning
confidence: 99%
“…We provide a method for dissociating skin organoids to facilitate such studies. The skin organoid single-cell RNA sequencing (scRNA-seq) data can be compared with skin atlases available through the Human Cell Atlas data portal 41,42 . Based on our scRNA-seq and immunostaining data, the end-stage skin organoids (~150 d of culture) represent the human skin tissues at the second-trimester stage of the developing fetus 25 .…”
Section: Applications Of the Skin Organoidsmentioning
confidence: 99%
“…The aim of the HDCA is to create a comprehensive single-cell reference map during normal organogenesis and early development stages to lay the foundation for aging, cancer, and regenerative medicine. [64] The organoid cell atlas presents the first framework for drug development and therapies for cancer, rare genetic diseases, and multifactorial disorders. [65] During the years 2017-2019, research teams from Qiao and Tang's laboratory reported a series of multiomics studies to map the development of human germline cells and embryo implantation.…”
Section: Advances In the Human Cell Atlasmentioning
confidence: 99%
“…For example, Botting et al recently generated a reference map of foetal liver haematopoiesis and establishment of immune cells in the skin and lung 56,57 . A component of the HCA’s ongoing work on a Developmental Cell Atlas will use stem cell‐derived organoids as a complementary cell source for difficult to obtain human foetal tissue 58,59 . This work will provide a tremendous resource for future investigations into the stem/progenitor cells that arise during human skin formation.…”
Section: Peering Inside the Black Box Of Human Skin Developmentmentioning
confidence: 99%